1997
DOI: 10.1021/bi971251w
|View full text |Cite
|
Sign up to set email alerts
|

MAP4 Is the in Vivo Substrate for CDC2 Kinase in HeLa Cells:  Identification of an M-Phase Specific and a Cell Cycle-Independent Phosphorylation Site in MAP4

Abstract: We reported previously that cdc2 kinase decreased the microtubule-stabilizing ability of a major HeLa cell microtubule-associated protein, MAP4, by phosphorylation in vitro [Ookata, K., et al. (1995) J. Cell Biol. 128, 849-862]. An important question raised by this study is whether MAP4 is indeed phosphorylated by cdc2 kinase at mitosis in vivo. We present here evidence that cdc2 kinase is the major M-phase MAP4 kinase, and, further, we identify two phosphorylation sites within the proline-rich domain of MAP4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
73
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 68 publications
4
73
0
Order By: Relevance
“…Cdc2 kinase phosphorylates at least two serines in the PRD (Ookata et al, 1997;Kitazawa et al, 2000), whereas kinases of the MARK/Par-1 family phosphorylate multiple serines in the AD (Drewes et al, 1997(Drewes et al, , 1998Ebneth et al, 1999). These phosphorylation events inhibit the MAP4 -MT interaction and lead to destabilization of MTs (Drewes et al, 1997;Drewes et al, 1998;Ebneth et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cdc2 kinase phosphorylates at least two serines in the PRD (Ookata et al, 1997;Kitazawa et al, 2000), whereas kinases of the MARK/Par-1 family phosphorylate multiple serines in the AD (Drewes et al, 1997(Drewes et al, , 1998Ebneth et al, 1999). These phosphorylation events inhibit the MAP4 -MT interaction and lead to destabilization of MTs (Drewes et al, 1997;Drewes et al, 1998;Ebneth et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The proline-rich domain (PRD, aa 654 -895) contains at least one MT binding site, as well as a region that promotes MT assembly and bundling (Aizawa et al, 1991). This region also binds to cyclin B1 and contains at least two cdk2 phosphorylation sites (Ookata et al, 1995(Ookata et al, , 1997Kitazawa et al, 2000). The C-terminal affinity domain (AD, aa 902-1090) contains up to four motifs (depending on the isoform) that are phosphorylated by MARK/Par-1 family kinases.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, p34/cdc2-induced APC phosphorylation has been found to disrupt APC and microtubule interactions, a finding that highlights the importance of phosphorylation in regulation of APC interactions with microtubules (Trzepacz et al, 1997). MAP4 is another important microtubule-binding protein that has been found to be phosphorylated by mitotic kinases including p34/cdc2 and microtubule-affinity regulating kinases (Illenberger et al, 1996;Ookata et al, 1997). Evidence suggests that MAP4 phosphorylation induced by these mitotic kinases causes MAP4 to dissociate from microtubules and thereby increase microtubule dynamics during mitosis (Illenberger et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that microtubule-binding/associated proteins (MAPs) such as MAP2 and MAP4 are phosphorylated during mitosis (Faruki et al, 1992;Ookata et al, 1997). Phosphorylation is a critical event regulating these MAPs as it causes their dissociation from microtubules and thereby facilitates M-phase cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%
“…This dynamic property of mitotic MTs is thought to be caused, at least in part, by the decreased MT-stabilizing ability of MAP4 at mitosis, which could be induced by phosphorylation with p34 cdc2 /cyclin B kinase. MAP4 was shown to be phosphorylated by p34 cdc2 kinase in HeLa cells (Ookata et al, 1997), and its phosphorylation was shown to reduce MT polymerizing ability in vitro Ookata et al, 1995). In Xenopus eggs, too, mitotic phosphorylation of a MAP4-like protein (XMAP230 or p220) was shown to participate in mitotic control of MT dynamics (Shiina et al, 1992;Andersen et al, 1994;Faruki and Karsenti, 1994).…”
mentioning
confidence: 99%